INTERNALISASI PEMIKIRAN KH. MUHAMMAD SHOLEH DARAT DI KOMUNITAS PECINTANYA: Perspektif Sosiologi Pengetahuan - Akhmad Luthfi Aziz (Living Islam: Journal of Islamic Discourses, 2018)
KH. Muhammad Sholeh Darat al-Samarani is one of the great Ulama in Nusantara in the 19th  century. He studied from the pesantren to the pesantren even to study in the Holy Land, Macca, then returned to Java to spread his knowledge in Darat, Semarang, Central Java. Years later, there was a community that elaborated and tried to construct and spread of KH. Muhammad Sholeh Darat al-Samarani’s works and thoughts. In this paper, using the sociological theory of knowledge of Peter L. Berger, the process of internalizing the thoughts of KH. Muhammad Sholeh Darat al-Samarani in the Kiai Sholeh Darat Community (Komunitas Pecinta Kiai Sholeh Darat, KOPISODA) will be discussed. Finally, it can be stated that there is an internalization process in understanding, applying, and living of KH. Muhammad Sholeh Darat al-Samarani’s thoughts in the community.